Pengaruh Tarif, Sanksi, dan Sosialisasi Pajak Terhadap Persepsi Kemudahan Pelaku UMKM Kuliner Atas Penerapan Peraturan Pemerintah Nomor 55 Tahun 2022 - Viana Theresia; I Gusti Agung Ayu Pramita Indraswari; I.G.A.N. Alit Sumantri (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to analyze the effects of tax rates, tax sanctions, and tax socialization on culinary MSME actors’ perceived ease regarding the implementation of Government Regulation No. 55 of 2022. The background of this research is grounded in the importance of perceived ease as a psychological factor influencing MSME tax compliance amid changes in tax policy. This study employed a quantitative approach using a survey method, in which primary data were collected through questionnaires distributed to culinary MSME actors. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the relationships among latent variables. The results indicate that tax rates have a positive and significant effect on perceived ease, suggesting that low and simple tax rates enhance MSME actors’ ability to fulfill their tax obligations. Tax sanctions also show a positive and significant effect on perceived ease, as clear and firm sanctions provide legal certainty and reduce taxpayer uncertainty. In addition, tax socialization has a positive and significant effect, serving as an important instrument in shaping MSME actors’ perceptions of ease in implementing Government Regulation No. 55 of 2022. Based on these findings, it can be concluded that improving the quality of tax socialization, applying proportional tax rates, and enforcing clear and fair sanctions are essential factors in enhancing perceived ease and supporting tax compliance among culinary MSMEs.